Purchasing Vegetables in the Digital Era: A Systematic Literature Review on Online Buying Behavior in E-Commerce - Soeyatno, Rahmah Farahdita; Darjanto, Arief; Syaukat, Yusman; Nurmalina, Rita (Agro Bali : Agricultural Journal, 2023)
This study aims to examine and analyze consumer behavior in purchasing vegetables online through E-Commerce in Indonesia. This can contribute to the creation of online food product marketing in Indonesia. A systematic literature review (SLR) was conducted based on studies of purchasing vegetables online through E-Commerce. The data collection method used the Population, Intervention, Comparison, and Outcome (PICO) framework. The selected articles were relevant to the research objectives (with keywords "Vegetable Purchase" and "Vegetable E-Commerce"). The selection process results showed that out of 171 articles, they met the specified criteria. Consequently, 40 articles were chosen based on the research statement for further review. Findings indicate that various factors, including technology adoption, trust, and social factors, influence consumer behavior in online vegetable purchases in Indonesia. By understanding and meeting consumer needs and expectations and leveraging digital technology, a satisfying shopping experience can be created, thus encouraging repeat purchases.